Pengembangan Aplikasi Pendeteksi Kelelahan bagi Pengendara Mobil berbasis Android melalui Face Recognition - Rahmat Adi Setiawan; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
One of the main causes of vehicle traffic accidents are human factors such as sleepiness during driving, which is 35% of total traffic accidents in Indonesia. In order to prevent and minimize the percentage of traffic accidents and material loss caused by that factor, through this research will be developed a fatigue detection system for car drivers. This research will be focusing on the development of fatigue detection method through visual cues with Percentage of Eye Closure (PERCLOS) method, which in that method measures the eye closure percentage against time to indicate the fatigue of a car driver. The system will be able to give the car driver a signal for a detected fatigue, directing the car driver to an area to rest, contacting the close related person to the car driver when fatigue detected and an emergency function to do that without a need of fatigue detection. This system will be implemented in a smartphone with Android-based operating system. Waterfall model is used for the development process of this system. The requirement analysis produced produced 8 functional requirements and 1 non-functional requirement in the development process. Unit testing has 100% pass result and validation testing has 100% pass result which has 15 test cases. The system expected a web-based implementation that can be used to integrate the fatigue detection system to handle user data in fatigue detection system in a large scale.